[(-3/4)^6:(-3/4)^3:(-3/4)^8]^4:(1-1/4):(1+1/2)=
Răspunsuri la întrebare
Răspuns de
3
[(-3/4)⁶:(-3/4)³:(-3/4)⁸]⁴:(1-1/4):(1+1/2)=
[(-3/4⁶⁻³⁻⁸]⁴:[(4-1)/4]:[(2+1)/2]=
[(-3/4)⁻⁵]⁴:(3/4):3/2=
[(-4/3)⁵]⁴·4/3·2/3=
(4/3)²⁰·4/3·2/3=
(4/3)²⁰⁺¹·2/3=
(4/3)²¹·2/3=
[(2²)²²/3²¹]·2/3=
(2⁴⁴/3²¹)·2/3=
(2⁴⁴⁺¹)/(3²¹⁺¹)=2⁴⁵/3²²
[(-3/4⁶⁻³⁻⁸]⁴:[(4-1)/4]:[(2+1)/2]=
[(-3/4)⁻⁵]⁴:(3/4):3/2=
[(-4/3)⁵]⁴·4/3·2/3=
(4/3)²⁰·4/3·2/3=
(4/3)²⁰⁺¹·2/3=
(4/3)²¹·2/3=
[(2²)²²/3²¹]·2/3=
(2⁴⁴/3²¹)·2/3=
(2⁴⁴⁺¹)/(3²¹⁺¹)=2⁴⁵/3²²
Alte întrebări interesante
Matematică,
9 ani în urmă
Limba română,
9 ani în urmă
Limba română,
9 ani în urmă
Matematică,
9 ani în urmă
Limba română,
9 ani în urmă
Limba română,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă